Early adolescent alcohol use in context: How neighborhoods, parents, and peers impact youth. (12th March 2014) - Trucco, Elisa M.; Colder, Craig R.; Wieczorek, William F.; Lengua, Liliana J.; Hawk, Larry W.
Abstract: Developmental–ecological models are useful for integrating risk factors across multiple contexts and conceptualizing mediational pathways for adolescent alcohol use, yet these comprehensive models are rarely tested. This study used a developmental–ecological framework to investigate the influence of neighborhood, family, and peer contexts on alcohol use in early adolescence ( N = 387). Results from a multi-informant longitudinal cross-lagged mediation path model suggested that high levels of neighborhood disadvantage were associated with high levels of alcohol use 2 years later via an indirect pathway that included exposure to delinquent peers and adolescent delinquency. Results also indicated that adolescent involvement with delinquent peers and alcohol use led to decrements in parenting, rather than being consequences of poor parenting. Overall, the study supported hypothesized relationships among key microsystems thought to influence adolescent alcohol use, and thus findings underscore the utility of developmental–ecological models of alcohol use.